Effect of soil quality and planting material on the root architecture and the root anchorage of young hybrid poplar plantations on waste rock slopes. Issue 1 (2nd January 2023) - Babi, Khadija; Guittonny, Marie; Bussière, Bruno; Larocque, Guy R.
ABSTRACT: On mine waste rock slopes, trees with inadequate root development could be prone to uprooting. The anchorage of trees is mainly determined by the architecture of the root systems that drive their mechanical interactions with the soil. The objective of this study was to evaluate the effects of soil quality and of different planting materials on the architecture and resistance to shear stress of root systems of hybrid poplars four years after they were initially planted. The study was conducted in an open-pit-gold mine. A hybrid poplar plantation was established in 2013 on 33% soil-covered waste rock slopes, using a randomised complete block design, that is, 3 replicated blocks × 3 planting materials × 2 soil qualities. The stability of the hybrid poplars (resistance to uprooting) was evaluated using lateral traction tests. Complete excavations were performed to characterise their coarse root (>4 mm) architecture. Results showed no significant differences between treatments in terms of the maximum resistance force to uprooting, which varied between 7142 and 8989 N. After four growing seasons, no significant effects due to soil quality or planting material were observed in the number of lateral roots, mean root diameter, root biomass, aboveground biomass, and shoot/root ratio.